2007
DOI: 10.1086/518612
|View full text |Cite
|
Sign up to set email alerts
|

HLA Polymorphisms and Cervical Human Papillomavirus Infection in a Cohort of Montreal University Students

Abstract: The results of this study support the hypothesis that certain HLA class II polymorphisms mediate genetic susceptibility to the acquisition of HPV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
2
34
1
Order By: Relevance
“…17 Cohort studies in Brazil and Canada showed inconsistent findings for the association between HLA class II genes and persistent infection. 19,20 In these studies, the average age of participants was 20 to 30 years. The findings in this study suggest that DRB1*0403 and DRB1*0405 are respectively associated with the high viral load at study entry and persistent infection of HPV18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Cohort studies in Brazil and Canada showed inconsistent findings for the association between HLA class II genes and persistent infection. 19,20 In these studies, the average age of participants was 20 to 30 years. The findings in this study suggest that DRB1*0403 and DRB1*0405 are respectively associated with the high viral load at study entry and persistent infection of HPV18.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, a Canadian cohort study of female university students found no associations between specific HLA class II alleles and risk of HPV persistence. 20 Neither study examined the HLA profiles among persistent infection of specific HPV type. Therefore, different prevalence of HPV types and genetic diversity of study participants might confound the findings.…”
mentioning
confidence: 99%
“…For the sake of analytic efficiency we restricted HLA genotyping to women who met one of two conditions: (i) women who participated in the study for at least 3 visits, or (ii) women who had a persistent infection with the same HPV type for 2 consecutive visits (27). HLA alleles were typed from purified DNA obtained from cervical specimens collected at enrollment, using PCR amplification of sequence-specific primers for HLA-B (27,28).…”
Section: Hla Genotypingmentioning
confidence: 99%
“…HLA alleles were typed from purified DNA obtained from cervical specimens collected at enrollment, using PCR amplification of sequence-specific primers for HLA-B (27,28). These HLA types were chosen a priori based on consistent published evidence to support their role in susceptibility to both HPV infection (27)(28)(29)(30) and cervical cancer (24,26,31,32).…”
Section: Hla Genotypingmentioning
confidence: 99%
See 1 more Smart Citation